Efficacy of Intravenous Thrombolysis Combined with Mechanical Stent Interventional Thrombectomy on Acute Ischemic Stroke: intravenous thrombolysis combined with mechanical stent interventional thrombectomy in acute ischemic stroke - Huang, Jun; Zhang, Ming; Nie, Qingbin; Zhang, Xinye; He, Xin; Yang, Yufeng; Mao, Gengsheng (Journal of Medical Biochemistry, 2022)
Background: To investigate the efficacy and safety of intravenous thrombolysis combined with mechanical stent interventional thrombectomy in the treatment of acute ischemic stroke. Methods: A retrospective analysis was carried out for clinical data of 118 patients with acute ischemic stroke admitted to our hospital from January 2017 to March 2018. The patients enrolled were divided into two groups according to different therapies, with 59 cases in each group. Patients in control group were administered with recombinant tissue plasminogen activator (rt-PA) intravenous thrombolysis on the basis of routine symptomatic treatment, while those in thrombectomy group underwent mechanical stent interventional thrombectomy based on rt-PA intravenous thrombolysis. The vascular recanalization rate and clinical efficacy after treatment were compared between the two groups. National Institutes of Health Stroke Scale (NIHSS) was used to identify the degree of neurological impairment in all patients before and after treatment, and Barthel Index was used to assess their activity of daily living. Moreover, the changes in the levels of T-lymphocyte subpopulation in peripheral blood and immuno-inflammatory factors before and after treatment were compared, and prognosis of patients and incidence of adverse reactions were recorded. Results: Clinical efficacy of all the patients was assessed at 3 months after treatment. The response rate was 93.2% (54/59) and 76.3% (45/59), respectively, in thrombectomy group and control group. It can be seen that the response rate in thrombectomy group was significantly better than that in control group (P=0.024). In the two groups, hemorrhage of digestive tract occurred in 3 cases and 2 cases, and skin and mucosal ecchymosis in 4 cases and 2 cases, respectively, which were all improved after symptomatic treatment. The NIHSS sore and modified Rankin scale (mRS) score after treatment were significantly lower than those before treatment, while the Barthel Index after treatment was distinctly higher than that before treatment (P<0.05). The NIHSS score and mRS score in thrombectomy group obviously declined compared with those in control group at 1 month after treatment (P<0.001), while they had no statistically significant differences at 2 months and 3 months after treatment between the two groups (P>0.05). The Barthel Index in thrombectomy group was obviously higher than that in control group at 1 month and 2 months after treatment (p=0.003, P=0.012), while its difference between the two groups was not statistically significant at 3 months after treatment (P>0.05). Levels of cluster of differentiation 3 (CD3)+, CD3+CD4+, CD4+/CD8+ and natural killer (NK) cells in peripheral blood at 6 months after treatment evidently rose compared with those before treatment (P<0.05), while level of CD3+CD8+ evidently declined compared with that before treatment (P<0.05). In thrombectomy group, levels of CD3+, CD3+CD4+, CD4+/CD8+ and NK cells were markedly higher than those in control group, while the level of CD3+CD8+ was markedly lower than that in control group (P<0.05). Besides, in thrombectomy group, levels of serum osteopontin (OPN), malondialdehyde (MDA) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) were evidently lower than those in control group at 1 month after treatment, while the level of serum superoxide dismutase (SOD) was evidently higher than that in control group (P<0.05). The differences in the proportion of patients in thrombolysis in cerebral infarction (TICI) grade ≥2b, residual stenosis rate, rate of 24 h symptomatic intracranial hemorrhage and survival rate were not statistically significant between the two groups (P>0.05). Compared with that in control group, the acute vascular re-occlusion rate in thrombectomy group was significantly decreased at 3 months after treatment (10.2% vs. 22.0%, P=0.026). Conclusions: Intravenous thrombolysis combined with mechanical stent interventional thrombectomy can effectively promote the vascular recanalization, improve the neurological function and activity of daily living of patients, reinforce the immunological function, inhibit the oxidative stress response and improve the prognosis of patients.